Will FDI be Resilient in this Crisis? - Calderon, Cesar; Didier, Tatiana (World Bank, Washington, DC, 2012)
Although foreign direct investment (FDI) flows have tended to remain resilient during previous crises, they may not behave in a similar fashion during the current crisis. Why? In past crises, the stability of FDI flows was significantly associated with an increase in mergers and acquisitions (M&A), reflecting 'fire-sale FDI'. In the present crisis, by contrast, M&A activity decreased significantly in the last quarter of 2008, and this trend may continue as long as the global crisis constrain the purchasing ability of foreign (acquiring) firms. These developments further illustrate that the nature of the current crisis differs considerably from previous ones, suggesting that certain key lessons from past crisis lessons might not apply in the current context.